GAMBARAN KESESUAIAN RESEP RAWAT JALAN JKN TERHADAP FORMULARIUM NASIONAL DI POLIKLINIK RUMAH SAKIT KARTIKA HUSADA JATIASIH - Rahmat Widiyanto; Alifa Sabrina; Viquardo Wollyano Xezandrio (Jurnal Farmasi IKIFA, 2023)
In order to meet the basic needs of a good life for the people of Indonesia, the government established the National Social Security System. The Social Security Organizing Agency (BPJS) is an institution formed to organize social security assistance programs in Indonesia. The program is referred to as the National Health Insurance (JKN) program. The National Formulary is a list of selected medicines needed and available in health service facilities as a reference in the implementation of the National Health Insurance (JKN). The benefits of the national formulary for quality control and optimizing services to patients. This research aims to determine the percentage of suitability of JKN outpatient prescriptions to the National Formulary at the Kartika Husada Jatiasih Hospital polyclinic for the January – March 2022 period based on prescription sheets, medicine items for each prescription sheet, and prescribing generic and non-generic medicine. This research is descriptive, which explains how the suitability of the polyclinic JKN outpatient prescription to the National Formulary. The population in this research was all JKN outpatient prescription sheets written by doctors at the polyclinic in January as many as 851 sheets, February as many as 610 sheets, and March as many as 796 prescription sheets. The sampling technique uses total sampling. The results showed that the total percentage of suitability for the January – March 2022 period based on prescription sheets was 53.97%, based on medicine items of 79.74%, and prescribing generic and non-generic medicines of 75.33% generic and non-generic at 24.67%.